The Role of Emotion in Learning English as a Foreign Language at Jordanian Universities - Al-Jarrah , Razan Muhammed; Bader, Yousef F.; Bader, Sa’ada S. (Journal of Ecohumanism, 2024)
As emotions play a major role in the process of learning a foreign language, it becomes important to know how they influence the learners’ motivation, enthusiasm, and attitude in acquiring a new language. The main objective of this study is to explore the effect of emotion on the process of learning a foreign language among some Jordanian university students majoring in English. This was a cross sectional study using a survey of modified Beliefs About Language Learning Inventory (BALLI) questionnaire. The target population was first-year Jadara University students learning English as a foreign language. Answers to the survey questions were analyzed using SPSS software. The role of emotional factors in learning a second language was obvious. A majority reported being slightly to strongly motivated to learn English. Nevertheless, seventy-three percent of the participants indicated that they experienced anxiety and fear while learning English. That is why eighty-six percent of the participants demanded that English language instructors and curriculum designers of English programs in academic institutions consider positive emotional factors (like eagerness, reward and pleasantness) in teaching English as a foreign language.